A Large Head Circumference is More Strongly Associated With Unplanned Cesarean or Instrumental Delivery and Neonatal Complications Than High Birthweight. Issue 4 (December 2016) - Lipschuetz, M.; Cohen, S.M.; Ein-Mor, E.; Sapir, H.; Hochner-Celnikier, D.; Porat, S.; Amsalem, H.; Valsky, D.V.; Ezra, Y.; Elami-Suzin, M.; Paltiel, O.; Yagel, S.
Abstract : ( Am J Obstet Gynecol . 2015;213:833.e1–e.12) Perinatal outcomes are known to be affected by fetal size. A cross-sectional study based on electronic medical records was undertaken to study whether obstetric outcomes are affected more by fetal head circumference (HC) than by birthweight (BW).